Tear flow in a population aged between 20 and 30 living in Peruvian cities with high and low relative humidity, 2019 - Coaguila Talavera, Angela N. (2022)
Objective: To determine the amount of tear flow in a population aged between 20 and 30 and correlate it with the relative humidity in Arequipa and Lima (2019). Materials and methods: A quantitative, observational, descriptive and cross-sectional study conducted from July toAugust 2019. The study population consisted of patients aged between 20 and 30 attending ophthalmology clinics in Lima (79 people) and Arequipa (44 people). The exclusion criteria were the following: postoperative patients who underwent an eye surgery, contact lens wearers, people who used a computer over six consecutive hours a day, or those who were awake for less than two hours on the day of the test. Age, sex, place of residence, occupation, time of computer use, marital status, relative humidity and tear flow were assessed. An Excel database was analyzed using IBM SPSS Statistics statisticalsoftware with parametric tests (Pearson correlation coefficient) to evaluate the correlation between the quantitative variables. Frequencies were used as qualitative variable, and mean and mode as quantitative variables. Results: A mean relative humidity of 31.89 %, low tear flow in 21 patients (47.7 %) and normal tear flow in 23 patients (52.3 %) were found in Arequipa. In contrast, a mean relative humidity of 71.05 %, low tear flow in 23 people (29.1 %) and normal tear flow in 56 people (70.9 %) were found in Lima. The correlation between tear flow and relative humidity accounted for 0.841in Arequipa and 0.876 in Lima. As for the correlation between age and tear flow, the higher the age, the lower the tear flow: Arequipa (-0.866) and Lima (-0.892). Regarding the correlation between time of computer use and tear flow, the longer the hourson the computer, the lower the tear flow: Arequipa (-0.757) and Lima (-0.806). However, neither correlation was significant. Conclusions: The lower the relative humidity, the lower the tear flow. Age and time of computer use were inversely proportional to tear flow.